Analysis of the therapeutic effect of synchronous integrated intensity modulated radiotherapy combined with chemotherapy in stage IIIc of cervical cancer - Mu, Yanru; Wang, Hui; Xu, Li; Shi, Li; Song, Rui; Wang, Dezhi; Gao, Yuhua; Yan, Haibo (Frontiers in Oncology, 2024)
Objective: To explore the Therapeutic effect of synchronous Integrated intensity modulated radiotherapy combined with chemotherapy in stage IIIc of Cervical Cancer Methods: A total of 58 patients with stage IIIC cervical cancer (KPS ≥ 80) were analyzed in this study. Synchronous integrated boost intensity-modulated radiotherapy (SIB-IMRT) and sequential boost intensity-modulated radiotherapy (LCB-IMRT) were used to treat pelvic and/or para-aortic metastatic lymph nodes, with 30 cases in the SIB group and 28 cases in the LCB group. Comparison of short-term and long-term efficacy. Comparison of recurrence and metastasis rates , radiation dose to organs at risk and incidence of adverse drug reactions. Result: 30 patients were treated with simultaneous integrated boost intensity-modulated radiotherapy (SIB-IMRT), and 28 patients were treated with sequential boost intensity-modulated radiotherapy (LCB-IMRT). At the completion of radiotherapy and 3 months after radiotherapy, there was no significant difference in clinical efficacy observed between the two treatment groups. The median overall survival (OS), progression-free survival (PFS), and disease-free survival (DMR) in the SIB-IMRT group were significantly higher compared to the LCB-IMRT group. The SIB-IMRT group demonstrated significantly lower rates compared to the LCB-IMRT group. Furthermore, within 3 years and 5 years, the rates of lymph node recurrence, cervical and vaginal local recurrence, and distant metastasis within the radiotherapy field were significantly lower in the SIB-IMRT group compared to the LCB-IMRT group. There were no significant differences observed between the two groups in terms of the maximum dose to the small intestine (Dmax), dose received by 2cc of the small intestine (D2cc), maximum dose to the rectum (Dmax), and dose received by 1cc of the bladder (D1cc). The incidence of bone marrow toxicity in the SIB-IMRT group was significantly lower compared to the LCB-IMRT group. Moreover, the occurrence of grade III and IV bone marrow toxicity was also significantly lower in the SIB-IMRT group compared to the LCB-IMRT group. Conclusion: The study has concluded that there is no significant differences in in terms of bladder associated adverse events and gastrointestinal toxicity in both Simultaneous Integrated Boost Intensity-Modulated Radiotherapy and Layered Conical Beam Intensity-Modulated Radiation Therapy.